Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Discordance Between Patient-Reported Outcomes and Physician-Rated Motor Symptom Severity in Early-to-Middle-Stage Spinocerebellar Ataxia Type 3 - Roderick P. P. W. M. Maas; Dennis J. L. G. Schutter; Bart P. C. van de Warrenburg (The Cerebellum, 2021)
Assessment of patient-reported outcome measures (PROMs) in spinocerebellar ataxias (SCAs) could provide valuable insights into self-perceived health status. Although they are considered additional endpoints in future clinical trials, determinants and interactions of different PROMs in early disease stages remain largely unknown. The aims of the present study were to evaluate health-related quality of life, depressive symptoms, fatigue, and physical activity in mildly to moderately affected SCA3 patients and to examine interrelations between these PROMs and objective disease severity indices. Twenty SCA3 patients and twenty healthy controls of comparable age and sex completed the EQ-5D-5L, Patient Health Questionnaire-9, Profile of Mood States, and International Physical Activity Questionnaire. Disease severity was quantified by the Scale for the Assessment and Rating of Ataxia (SARA) and Inventory of Non-Ataxia Signs (INAS). Mildly to moderately affected SCA3 patients reported lower quality of life ( p = 0.049), more depressive symptoms ( p = 0.028), and higher levels of fatigue ( p = 0.001) than healthy controls. The amount of physical activity did not differ between both groups. Linear regression analyses revealed that quality of life was primarily determined by fatigue and not by ataxia severity, while physical activity was independently associated with SARA score and INAS count but not fatigue. Depressive symptoms were related to disease duration and fatigue but not to markers of motor disease progression. Taken together, decreased quality of life, increased levels of fatigue, and a higher number of depressive symptoms do not merely reflect motor impairment in early-to-middle-stage SCA3 patients. The observed discordance between patient-reported and clinician-based outcomes indicates that these measures genuinely evaluate distinct aspects of disease and emphasizes their complementariness in therapeutic trials. By contrast, the volume of self-reported physical activity is not associated with fatigue, reflects both ataxia severity and extracerebellar involvement, and could therefore represent a useful marker of motor impairment in a home setting.